Hubungan Persepsi Siswa Terhadap Program Dengan Keterlibatan Siswa Mengikuti Program Ekstrakurikuler Pramuka Pilihan Di SMKN 1 Payakumbuh - Ella Buchica Ditara; Ismaniar Ismaniar (Jurnal Family Education, 2023)
The background to writing this article is the low number of students participating in the scout extracurricular program at SMKN 1 Payakumbuh. This study aims to: describe students' perceptions of the program, describe students' involvement in participating in the program, and look at the relationship between students' perceptions of the program and student involvement in the scout extracurricular elective program at SMKN 1 Payakumbuh. The present study employs a quantitative research approach utilizing correlational descriptive techniques. The study's target populace consisted of all registered scout members during the 2022/2023 academic year, amounting to 20 individuals, of which a sample size of 15 people was selected. The method utilized for collecting data involves the deployment of a tool designed for such a purpose, which takes on the form of a terminal. The data analysis methodology employs a combination of the proportion formula and Spearman's Rank Correlation Coefficient, commonly known as Spearman's rho.The results showed that: (1) the perceptions of students participating in the scout extracurricular options towards the concentration program were very good, (2) student involvement in the selected scout extracurricular activities was included well and (3) there was a significant relationship between the perceptions of students participating in scout extracurricular activities towards the program with the involvement of students following the selected scout extracurricular program at SMKN 1 Payakumbuh. It is hoped that the Payakumbuh Vocational School 1 school will socialize the selected scout extracurricular program to all students so that they have good knowledge of the program, to coaches and selected scout extracurricular members it is hoped that together they can realize a good perception of the program by increasing knowledge and skills in scouting science and techniques so that the number of students participating in scout extracurriculars increases every year, other researchers are encouraged to search for additional variables that impact the participation of extracurricular members in scouting activities.